Effects of Nitric Oxide Donor Antioxidants Containing the Phenol Vitamin E Substructure and a Furoxan Moiety on Ischemia/Reperfusion Injury - Di Stilo, Antonella; Chegaev, Konstantin; Lazzarato, Loretta; Fruttero, Roberta; Gasco, Alberto; Rastaldo, Raffaella; Cappello, Sandra (Arzneimittelforschung, 2009)
Nitric oxide (NO) donor antioxidants are a class of polyvalent drugs which is the focus of great interest today. They are potentially useful for the treatment of many forms of cardiovascular diseases, including the myocardial ischemia/reperfusion (I/R) damage which seems to be due to both a burst of reactive oxygen species (ROS) and a reduced release of NO during reperfusion. In this paper the results of a study on the ability of new NO-donor antioxidants containing the phenol vitamin E substructure and furoxan moiety to attenuate I/R damage are reported. The compounds under study are obtained by combining the phenol moiety (6-hydroxy-2,2,5,7,8-pentamethylchroman) present in vitamin E with differently substituted furoxan substructures endowed with different capacity of NO-release. Their antioxidant and NO-dependent vasodilator activities are reported. The I/R experiments were performed on isolated rat heart preparations perfused at a constant flow. After 20 min of stabilization, global ischemia was obtained by interrupting the perfusion for 30 min. After ischemia the hearts were reperfused for 2 h. The compounds were added to the perfusion buffer during the first 20 min of reperfusion. At the end of each experiment, the infarct size was measured with nitro-blue tetrazolium. From the results it appears that the limitation of the infarct area is favoured by an appropriate balance between NO-donor and antioxidant properties and that these two actions are synergic.
Keywords: Antioxidants; Furoxans; Ischemia/reperfusion; Multitarget drugs; Myocardial protection; Nitric oxide donors